How the characteristics of sports bras affect their performance. Issue 3 (4th March 2021) - Norris, Michelle; Blackmore, Tim; Horler, Brogan; Wakefield-Scurr, Joanna
Abstract: Breast movement reduction (%) measures breast support and sports bra performance, however limited evidence exists on the sports bra characteristics which affect it. This study investigated breast movement reduction achieved by 98 sports bras, the categorisation of support levels, and the characteristics that contribute. Each bra was tested on ∼12 females (total n = 77). Relative breast position was recorded during sports bra and bare-breasted running, and breast movement reduction calculated; low, medium, high breast support tertiles were identified and compared to brand-classified support levels. Ten bra characteristics were identified, and regressions determined which characteristics contributed to performance. Breast movement reduction ranged from 36% to 74%; 69% of bras marketed as high support were in the high support tertile (>63%). Encapsulation style, padded cups, nylon, adjustable underband and high neck drop accounted for 37.1% of breast movement reduction variance. Findings facilitate high performance sports bra development and inform consumer choice. Practitioner summary: Little is known about the biomechanical breast support which sports bras actually provide. This original research facilitates high performance sports bra development, and helps inform consumer choice, by identifying the breast movement reduction of a large sample of sports bras, and the characteristics which impact sports bra performance. Abbreviations: A-P: anterior-posterior; BMI: body mass index; C7: 7th cervical vertebrae; LNIP: left nipple; M-L: medial-lateral; PX: xiphoid process; ROM: range of motion; S-I: superior-inferior; SD: standard deviation; STN: suprasternal notch; T8: 8th thoracic vertebrae